INTEGRATED FOOD BUSINESS MANAGEMENT - Rimawan, M. (Universitas Borneo Tarakan, 2024)
Talabiu village is a coastal area whose main income is milkfish and has been developed into processed presto milkfish products. The results of processed bandneg production are still not optimal due to the limited understanding of the MSME group regarding management, production and business development. The aim of this service is to increase the understanding and skills of Milkfish Presto Hayati UKM in improving aspects of production, digital marketing, packaging and simple financial reporting, in order to strengthen the sustainability of their business and maximize the village's economic potential. The methods used in this service include training and mentoring and training related to digital marketing, packaging, simple financial reporting. The evaluation results show that this activity is very useful in increasing the knowledge and expertise of the presto Hayati milkfish MSE group, especially improving production aspects such as providing tools, online marketing, packaging benefits and being able to provide simple reports with the help of the application.